2017
DOI: 10.1111/jam.13419
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and antimicrobial resistance profiles of Campylobacter coli and Campylobacter jejuni isolated from broiler chicken in farms and at time of slaughter in central Italy

Abstract: Campylobacter coli was detected more frequently than C. jejuni in contrast to common findings for poultry. The high prevalence of 30% resistance to erythromycin in C. coli strains isolated from poultry is worrisome, as this is the first antibiotic of choice to treat human campylobacteriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
24
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 46 publications
9
24
0
2
Order By: Relevance
“…All tested isolates of C. jejuni from batch 1 were susceptible to macrolide (AZM and E), compare with 81.6 and 100% of the tested isolates of C. coli from batches 2 and 3, respectively, resistant to this antimicrobial. These data were in accordance with recent reports ( Ruzauskas et al, 2011 ; Haruna et al, 2012 ; Fraqueza et al, 2014 ; Pergola et al, 2017 ), which indicated that C. jejuni was predominantly susceptible to erythromycin while C. coli was resistant. However, another possible reason for the results in the current study is that Campylobacter isolated from the same batch may have primarily the same antibiotic resistance profile.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All tested isolates of C. jejuni from batch 1 were susceptible to macrolide (AZM and E), compare with 81.6 and 100% of the tested isolates of C. coli from batches 2 and 3, respectively, resistant to this antimicrobial. These data were in accordance with recent reports ( Ruzauskas et al, 2011 ; Haruna et al, 2012 ; Fraqueza et al, 2014 ; Pergola et al, 2017 ), which indicated that C. jejuni was predominantly susceptible to erythromycin while C. coli was resistant. However, another possible reason for the results in the current study is that Campylobacter isolated from the same batch may have primarily the same antibiotic resistance profile.…”
Section: Discussionsupporting
confidence: 93%
“…Campylobacter isolates from one farm showed primarily the same genotype and the same antibiotic resistance profile as previously reported ( Pergola et al, 2017 ). Some studies have supported the hypothesis that the contamination of Campylobacter in broiler carcasses is mainly from the processed Campylobacter -positive birds within a batch ( Rasschaert et al, 2006 ; Sasaki et al, 2014 ).…”
Section: Discussionsupporting
confidence: 76%
“…In recent Catalonian (north-east Spain) and Italian studies, the predominant clonal complex of C . coli isolates was also ST828 [ 20 , 21 ]…”
Section: Resultsmentioning
confidence: 99%
“…However, in accordance to our study, many other authors have reported C.coli dominance. Pergola et al (40) reported 70.71% prevalence of C. coli and 17.14% C. jejuni from cloacal swab samples. Monika (21) and 19) also reported higher C.coli presence of 75% and 67.44%,respectively of the total isolates recovered from poultry faeces of Uttarakhand.…”
Section: Prevalence Of Thermophilic Campylobactersmentioning
confidence: 98%